Fatigue crack-propagation law of diaphragm-to-rib welded joint in steel bridge deck. (July 2022) - Fang, Liang; Fu, Zhongqiu; Ji, Bohai; Gao, Yuqiang
Abstract: The crack-growth characteristics at different lengths are diverse, while blind maintenance for cracks cannot achieve satisfactory arresting effect. By carrying out numerical simulation and fatigue tests of diaphragm-to-rib welded joint (DU) specimens, the crack-growth rates, morphology and stress state at the crack tip were explored. The crack-growth process was segmented and reasonable maintenance occasions for DU cracks were proposed. The result shows that the oblique DU crack is affected by in-plane shear under out-of-plane deformation of diaphragm, driving the crack to grow to the horizontal. The DU crack presents the three-stage characteristics of fast-slow-rapid growth with the approximate demarcations of 8 mm and 40 mm. It is recommended to carry out maintenance in the first two stages to avoid entering the third rapid-growth stage. Combined with the applicability of maintenance technologies, classified maintenance methods of ICR, drilling and bolt reinforcement were proposed for cracks in three stages, respectively. Graphical abstract: Unlabelled Image Highlights: Explore the reason for crack turning under out-of-plane deformation of diaphragm. Propose three-stage growth characteristic and its demarcations of diaphragm cracks. Suggest the reasonable maintenance occasion for diaphragm cracks. Provide classified maintenance methods for diaphragm cracks of different lengths.